Optimization and Mechanical Properties of TiO2 Reinforced AA 7150 Composites Using Response Surface Methodology - S V G V A Prasad; V. Kamalakar; J. Madhusudhanan; Puthalapattu Reddy Prasad; G. Adilakshmi; Nellore Manoj Kumar; Anitha Gopalan; Vinod Singh rajput; Nagaraj Ashok (Advances in Materials Science and Engineering)
The goal of this research is to increase the performance of AA 7150 reinforced with TiO2 microparticles by optimizing the stir casting parameters. The response surface method's central composite design technique was used to optimize the three stir casting factors of stirring temperature (A), stirring speed (B), and stirring time (C). The ultimate tensile strength, hardness, impact strength, elastic modulus, and compressive strength were all tested. With the aid of analysis of variance, it was discovered that it had a substantial influence on the test samples' characteristics responses. 5 quadratic experiments were linked using factors' characteristics. At a level of 95% confidence, the models were found to be statistically important, and the variations were found to be less than 5%. The response surface was used to assess the parameter interaction profile. Each interaction's contour plots provided a range of stirring settings within which each property may be maximized.